(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to evaluate the effect of different irrigation water salinity levels on tomato (Solanum lycopersicum L.) seed germination and early seedling growth under nursery conditions in Al-Zawiya, Libya. The experiment was conducted from 15 April to 5 May 2025 using a completely randomized design (CRD) with five irrigation water salinity treatments: 1, 2, 4, 6, and 8 dS/m. Each treatment included four replicates, with 25 seeds per replicate. Germination was recorded daily for 14 days, while seedling growth traits were measured on day 21, including root length, shoot length, total seedling length, fresh weight, dry weight, and seedling vigor index. Data were analyzed using one-way analysis of variance (ANOVA), and mean comparisons were performed using Tukey’s test at p ≤ 0.05. The results showed that increasing irrigation water salinity caused a significant reduction in germination percentage and early seedling growth traits, accompanied by a clear increase in mean germination time. Germination percentage decreased from 92.00% at 1 dS/m to 45.00% at 8 dS/m, while mean germination time increased from 5.53 to 8.93 days. Total seedling length declined from 15.10 cm to 5.90 cm, fresh weight decreased from 1.83 to 0.55 g/10 seedlings, and dry weight decreased from 0.17 to 0.05 g/10 seedlings. Seedling vigor index also declined markedly from 1390.60 to 267.20 as salinity increased from 1 to 8 dS/m. The study concludes that high irrigation water salinity, particularly at 6 and 8 dS/m, restricts tomato seed germination and weakens early seedling growth, highlighting the importance of irrigation water quality during tomato seedling production.